Effects of acute heat stress at different ambient temperature on hepatic redox status in broilers - Miao, Qixiang (Poult Sci, 2020)
This study aimed to investigate the effects of different acute high ambient temperatures on redox status in liver of broilers. A total of 144 35-day-old Arbor Acres broilers were randomly divided into 4 groups with 6 replicates of 6 birds each and subsequently distributed in different environment chambers for acute heat stress. The temperature of 4 environment chambers were set to 26°C (control), 29°C, 32°C, 35°C for 6 h, respectively. Various indicators were tested to evaluate hepatic redox status. Then, the hallmarks of hepatocellular antioxidant and apoptosis were measured by qRT-PCR and Western Blot. The results showed that with the ambient temperature increase (i) the content of hydrogen peroxide (H(2)O(2)) and protein carbonyl (PC) in the liver of broilers increased significantly (P < 0.05), but the content of malondialdehyde (MDA) and 8-hydroxyguanosine (8-OHdG) was not affected; (ii) the activity of catalase (CAT) and glutathione reductase (GR) increased significantly (P < 0.05). Similarly, the superoxide dismutase (SOD) had an increasing tendency (P = 0.07), and the content of the reduced glutathione (GSH) was also significantly increased (P < 0.05) under high temperature; (iii) the heat shock protein (HSP70), nuclear factor erythroid-2-related factor 2 (Nrf2), and other antioxidant gene (HO-1, NQO1, GCLc, GST, SOD1, SOD2, CAT, Prx3) were upregulated in broilers liver. Moreover, the protein level of HSP70, Nrf2, and Prx3 were also upregulated; (iv) high temperature upregulated the antiapoptotic gene expression (BCL-2); however, the proapoptotic genes (BAK1, caspase-3, and caspase-9) did not change significantly; meanwhile, there was no significant changes in the protein level of caspase-3 and caspase-9. The results of this study indicated that 35-day-old Arbor Acres broilers have a certain tolerance to oxidative stress induced by high ambient temperature. Six hours of acute heat stress–activated Nrf2 signaling pathway. Meanwhile, the expression of related antioxidant genes and proteins is upregulated, consequently resulted in increased antioxidant enzymes activity and GSH. These effects enable the body to scavenge large amounts of reactive oxygen species produced by high temperature and prevent the occurrence of apoptosis.